2016
DOI: 10.1016/j.jcv.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A four year seasonal survey of the relationship between outdoor climate and epidemiology of viral respiratory tract infections in a temperate climate

Abstract: A sudden drop in outdoor temperature might activate the annual influenza epidemic in a temperate climate by facilitating aerosol spread in dry air. These conditions also seem to affect the incidence of other respiratory pathogens but not human rhino- or enterovirus, suggesting that routes of infection other than aerosol may be relevant for these agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
57
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 45 publications
14
57
1
4
Order By: Relevance
“…As we have reported earlier, RV is the most frequently detected virus in patients with respiratory symptoms, without marked seasonality in a temperate climate (32). In the present study, RV was the major finding in asymptomatic and in symptomatic adults.…”
Section: Discussionsupporting
confidence: 82%
“…As we have reported earlier, RV is the most frequently detected virus in patients with respiratory symptoms, without marked seasonality in a temperate climate (32). In the present study, RV was the major finding in asymptomatic and in symptomatic adults.…”
Section: Discussionsupporting
confidence: 82%
“…Our study indicated that decline in RH promoted influenza activity, and the result is consistent with previous studies. Several previous studies indicated that low RH can favour the transmission of influenza (Hemmes et al, 1960;Lowen et al, 2007;Schaffer et al, 1976;Sundell et al, 2016). Low RH can allow influenza virus particles to remain in the air for longer time because of the smaller size and lower velocity of settling (Yang and Marr, 2011).…”
Section: N=100%mentioning
confidence: 99%
“…A further limitation is that, for simplicity, only weather information from the capitals were used in the study, but for countries like Japan, Thailand and Taiwan, there are great variation between climatic conditions in the North and the South. Prediction accuracy might improve if [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] incidence and weather information can be collected at a finer resolution. We suspect that even the accuracy of short term forecasts may be reduced should new epidemiological conditions replace those that the model was trained on.…”
Section: Limitationsmentioning
confidence: 99%
“…Existing approaches to real-time forecasting include generalized linear regression, seasonal autoregressive integrated moving average (SARIMA) model or a simpler ARIMA form of it, phenomenological models like the logistic growth model and Richards model, and mechanistic models like the SIR models [19][20][21][22][23][24]. Often such approaches involve the challenge of integrating environmental factors including temperature, humidity and rainfall, which may influence pathogen transmission directly or affect the vector activities (for vector borne diseases), especially in temperate regions [25][26][27][28][29]. For instance, influenza virus is more transmissible in low temperature and low humidity conditions [30,31], while the primary vector of dengue, the yellow fever mosquito Aedes aegypti, favors higher temperature [32,33].…”
Section: Introductionmentioning
confidence: 99%